Re-shedding Trials of Toxoplasma gondii Oocysts from Experimentally Infected Kittens Reference to Strain Types I, II and III; Zoonotic and Histopathological Confirm - Shaapan, Raafat; Elfadaly, Hassan; Elaadli, Haitham; Salman, Marwa B.; Maher, Ahmed; Barakat, Ashraf (Journal of Advanced Veterinary Research, 2023)
Cats are the only definitive host of Toxoplasma gondii (T. gondii) that shed millions of un-sporulated oocysts. The current study aimed at evaluating the serological and histopathological potential ratio of T. gondii oocysts shedding and re-shedding kittens. Blood and fecal samples collected from fifty-seven un-weaned kittens from various districts of Cairo Governorate, Egypt. All kittens serologically screened for T. gondii using the Latex agglutination test (LAT), and fecal materials inspected daily for oocysts. Only proven seronegative un-shedding kittens employed in the three experimental re-shedding studies using the three T. gondii strain types II, III, and I with the third trial focusing on the ability of re-shedding with corticosteroid therapy. Â One kitten corresponding to each type sacrificed for histo-pathological assay and IgM/IgG serum antibodies recorded along the trials course using ELISA. The overall sero-negative percentage was 59.7%, with 35.1 and 24.6% in shedding and un-shedding ones respectively. The shedding number of oocysts /100 mg/feces scored (7, 5 and 3); (30, 15 and 7); (20, 10 and 5) corresponding and sequence to the three T. gondii strain types I, II and III respectively. In addition, the average IgM/IgG ELISA titers recorded significance variations sequence to the three strain types. Corticosteroids therapy stimulates re-shedding ability for the third time. The findings concluded that kittens shed oocysts at a high rate; regard shedding and re-shedding qualities as a critical component in developing oocyst-borne human and animal toxoplasmosis effects. Strong protection against vaccinated cats are required, as is close interaction between cats and farm animals.